Seepage Damage Statistical Model of Filled Fractured Rock considering Structural Surface and Failure Characteristic - Xinyu Liu; Yuan Tian; Zhende Zhu (Advances in Civil Engineering)
Damage theory studies the whole process of initiation, propagation, and instability of microcracks in materials and provides an important basis for the estimation of the risk of materials. Therefore, it is assumed that the rock microunit strength is the damage variable of the medium and obeys the Weibull distribution. According to the tensile failure characteristics of filled fractured rock under the action of seepage stress, the maximum tensile strain criterion is used to define the rock microunit strength parameters, and the equivalent elastic modulus of the fractured rock is used to establish a new damage statistical model. This paper mainly studies the rationality and feasibility of using this new constitutive model to describe the seepage failure process and damage characteristics of filled fractured rock. The results indicate that (1) the accuracy of the equivalent elastic modulus is affected by the confining pressure and the characteristics of the structural surface. In the elastic phase, using the equivalent elastic modulus, EVRH has better fit. In the plastic phase, it is better to use the EV parameter. (2) The established Weibull distribution statistical model can better calculate the stress-strain curve of fractured rocks with weak and soluble fillings. (3) The rock strength characteristics affected by different stress conditions and different filling fracture states calculated by the model are the same as the experimental data. (4) The model using equivalent elastic modulus parameters reflects the threshold characteristics of rock failure and the damage evolution process. After comparison, it is found that the model can accurately calculate the final damage value of the fractured rock with weak and soluble filling. However, the final damage value used to calculate the fractured rock of the hydraulic material filling is much higher and inaccurate.